Simultaneously determination of bisphenol A and uric acid by zinc/aluminum-layered double hydroxide-2-(2,4dichlorophenoxy) propionate paste electrode - Illyas Md Isa (Tanjong Malim, 2019)
Simultaneously determination of bisphenol A and uric acid by zinc/aluminum-layered double hydroxide-2-(2,4dichlorophenoxy) propionate paste electrode by Illyas Md Isa